Evaluating Tourist Perception of Environmental Changes as a Contribution to Managing Natural Resources in Glacierized Areas : a Case Study of the Forni Glacier (Stelvio National Park, Italian Alps) - V. GARAVAGLIA; G. DIOLAIUTI; C. SMIRAGLIA; M. PELFINI; V. PASQUALE (Environmental Management, 2012)
Climate change effects are noticeably evident above the timberline where glacier and permafrost processes and mass movements drive the surface evolution. In particular, the cryosphere shrinkage is deeply changing the features and characteristics of several glacierized mountain areas of the world, and these modifications can also affect the landscape perception of tourists and mountaineers. On the one hand glacier retreat is increasing the interest of tourists and visitors in areas witnessing clear climate change impacts; on the other hand cryosphere shrinkage can impact the touristic appeal of mountain territories which, diminishing their ice and snow coverage, are also losing part of their aesthetic value. Then, to promote glacierized areas in a changing climate and to prepare exhaustive and actual proposals for sustainable tourism, it is important to deepen our knowledge about landscape perception of tourists and mountaineers and their awareness of the ongoing environmental modifications. Here we present the results from a pilot study we performed in summer 2009 on a representative glacierized area of the Alps, the Forni Valley (Stelvio National Park, Lombardy, Italy), a valley shaped by Forni, the largest Italian valley glacier. During the 2009 summer season we asked tourists visiting the Forni Valley to complete a questionnaire. This study was aimed at both describing the features and characteristics of tourists and mountaineers visiting this Alpine zone in summer and evaluating their landscape perception and their ability to recognize climate change impacts and evidence. Our results suggest that the dissemination strategies in a natural protected area have to take into account not only the main landscape features but also the sites where the information will be given. In particular considering the peculiarities of the huts located in the area, such as their different accessibility and the fact that they are included or not in a mountaineering network like that of the Italian Alpine Club. Both these factors ...